KONTROVERSI PENAFSIRAN TENTANG PENCIPTAAN PEREMPUAN DALAM AL-QUR`AN: Analisis terhadap Penafsiran M. Quraish Shihab - Wardani, Wardani (Muadalah, 2014)
This article analyzes the response of M. Quraish Shihab interpretation on the controversy of sensitive issue in feminism discourse that arises among classical and contemporary Moslem scholars, that is the process of women creation. An interpretation mainstream has been grew among the classical Moslem scholars that women were created from the ribsâa literal interpretation and emphasizes the process of physical events which then has implications for their subordinate position compared to men. Whereas, a metaphor interpretation which emphasizes on the women psychology rather than the actual physical events grows among the contemporary scholars. This study tries to elaborate the interpretation argumentations and to locate the interpretation in the debate arises among classical and contemporary interpretation.